Preparation and performance of sludge-based desulfurizer by calcification. Issue 4 (August 2020) - Song, Xin; Ge, Shifu; Li, Yuan
Abstract: The study used Ca/TS, water content, particle size and additives as control variables to prepare sludge-based desulfurizers. An experimental setup was built up to investigate the desulfurization effect. The 5-factor and 4-level orthogonal experimental scheme was designed to study the factors affecting the sulfur capturing efficiency of sludge-based desulfurizer. The effects of the types and ratios of additives on the sulfur capturing rate were studied with sodium carbonate, iron oxide and acetic acid as additives. The result showed that the optimal condition to produce calcification sludge desulfurizer (CSD) was: 0.425~0.6mm of diameter desulfurizer, moisture content of 30%, and ferric oxide ratio of 6%. The optimal desulfurization condition was the combustion temperature of 900 °C, calcium to sulfur molar ratio of 2.0 and the SO2 concentration of 1%. In this case, the sulfur capturing ratio was 61.86%, higher than that of pure calcium oxide. The pore structure of the sludge-based desulfurizer showed that compared with the porosity of pure calcium oxide of 32.02% and the specific surface area of 19.80 m 2 /g, the sludge-based desulfurizers increased to 36.94% and 28.32 m 2 /g, respectively. The degree of irregularity is low, which greatly improves the sulfur-fixing effect of the sludge-based desulfurizer.